2021
DOI: 10.5130/ijcre.v14i1.7728
|View full text |Cite
|
Sign up to set email alerts
|

Trauma informed participatory research: Reflections on co-producing a research proposal

Abstract: This article discusses the development of a co-produced research proposal. The authors reflect on the process of this work and some of the challenges that were experienced by a team who had a mix of lived, clinical and academic experience of the research topic. We highlight the need to embed trauma informed principles into co-produced research and the ways in which doing so can support the development of co-produced work. As such, the article focuses on how we established safety, choice, collaboration, trustwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Positive final reflections of the reciprocal benefit in coproducing implementation research corroborated previously published coauthor reflections in the study protocol [10]. Reflections on the emotional nature of the writing stage of research were also consistent with the emotion described during data collection [10], supporting the use of trauma-informed principles in coproduced research [79,80]. Researcher experiences appeared to corroborate suggestions that research practices, cultures, and structures encumber the process of coproduction, making it challenging to achieve the aspirations of coproduction [81].…”
Section: Collaborative Autoethnography Of the Researchsupporting
confidence: 76%
“…Positive final reflections of the reciprocal benefit in coproducing implementation research corroborated previously published coauthor reflections in the study protocol [10]. Reflections on the emotional nature of the writing stage of research were also consistent with the emotion described during data collection [10], supporting the use of trauma-informed principles in coproduced research [79,80]. Researcher experiences appeared to corroborate suggestions that research practices, cultures, and structures encumber the process of coproduction, making it challenging to achieve the aspirations of coproduction [81].…”
Section: Collaborative Autoethnography Of the Researchsupporting
confidence: 76%
“…Of major importance, is the consideration of the power differential between researcher (an adult) and participant (a child/youth) ( Crane and Broome, 2017 ). Autistic children and youth in particular, may enter the research process with previous experience of being disempowered when interacting with neurotypical adults ( Lonbay et al, 2021 ). With this in mind, we gathered informed consent from both parents and children/youth prior to each interview.…”
Section: Methodsmentioning
confidence: 99%
“…As Maguire and Britten [ 13 ] note, the expertise that lay people bring to research often draws on ‘ raw, painful and intimate experiences ’ (p.464). Whilst this can contribute strongly to the profundity, authenticity and validity of their contributions, it may also mean lay researchers can be powerfully impacted by research, and may even be retraumatised by it [ 21 , 22 ]. As a team of co-authors and co-researchers, we have discussed this issue and concluded that narrative data of the kind found in qualitative research may be particularly likely to trigger emotions in this way, because of their first-person immediacy.…”
Section: Discussionmentioning
confidence: 99%
“…As a team of co-authors and co-researchers, we have discussed this issue and concluded that narrative data of the kind found in qualitative research may be particularly likely to trigger emotions in this way, because of their first-person immediacy. Bearing this in mind, we endorse recommendations for professional and lay researchers to discuss openly the potential for emotional triggering before and during projects, encouraging each other to reflect on how they might be affected, secure in the knowledge that they are welcome to opt in or out at any time [ 13 , 21 ]. We also commend the use of reflective statements among lay and professional researchers as a means of processing feelings, as we have done in the development of this paper and the final evaluation, because they helped us to identify, share and discuss personal responses that might otherwise have remained unsaid.…”
Section: Discussionmentioning
confidence: 99%